2003
DOI: 10.1034/j.1600-048x.2003.02528.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐breeding energy requirements: thyroid hormone, metabolism and the timing of reproduction in house sparrows Passer domesticus

Abstract: M. 2003. Pre-breeding energy requirements: thyroid hormone, metabolism and the timing of reproduction in house sparrows Passer domesticus. -J. Avian Biol. 34: 298-306.We measured thyroid hormone (T3) levels and energy expenditure of pre-breeding house sparrows Passer domesticus in relation to the timing of breeding and reproductive success. The onset of reproduction was synchronised in two waves, separated by a three-week interval. On an annual basis, early breeders (birds that bred for the first time during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 56 publications
5
73
2
Order By: Relevance
“…In contrast, other studies report no relationship between metabolic rate and thyroid hormones in captive mammals (Nilssen et al, 1984;Ostrowski et al, 2006), including humans (Bernstein et al, 1983;Johnstone et al, 2005). However, little information is available concerning the relationship between thyroid hormones and metabolic rate for animals living under natural conditions (exceptions are studies on birds: Chastel et al, 2003;Elliott et al, 2013;Welcker et al, 2013;Zheng et al, 2014; and a study of free-ranging Arctic ground squirrels Urocitellus parryii; Wilsterman et al, 2015), and the reported results are ambivalent. Some studies report a positive relationship between T 3 levels and metabolic rate (Chastel et al, 2003;Welcker et al, 2013) while others found no relationship (Burger and Denver, 2002).…”
Section: Introductionmentioning
confidence: 43%
See 2 more Smart Citations
“…In contrast, other studies report no relationship between metabolic rate and thyroid hormones in captive mammals (Nilssen et al, 1984;Ostrowski et al, 2006), including humans (Bernstein et al, 1983;Johnstone et al, 2005). However, little information is available concerning the relationship between thyroid hormones and metabolic rate for animals living under natural conditions (exceptions are studies on birds: Chastel et al, 2003;Elliott et al, 2013;Welcker et al, 2013;Zheng et al, 2014; and a study of free-ranging Arctic ground squirrels Urocitellus parryii; Wilsterman et al, 2015), and the reported results are ambivalent. Some studies report a positive relationship between T 3 levels and metabolic rate (Chastel et al, 2003;Welcker et al, 2013) while others found no relationship (Burger and Denver, 2002).…”
Section: Introductionmentioning
confidence: 43%
“…However, little information is available concerning the relationship between thyroid hormones and metabolic rate for animals living under natural conditions (exceptions are studies on birds: Chastel et al, 2003;Elliott et al, 2013;Welcker et al, 2013;Zheng et al, 2014; and a study of free-ranging Arctic ground squirrels Urocitellus parryii; Wilsterman et al, 2015), and the reported results are ambivalent. Some studies report a positive relationship between T 3 levels and metabolic rate (Chastel et al, 2003;Welcker et al, 2013) while others found no relationship (Burger and Denver, 2002). This inconsistency in results highlights the need for additional studies examining the relationship between thyroid hormone levels and metabolic rate of free-living animals, especially mammals.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…For example, it has been shown in humans that serum tT 3 concentrations increase with an elevated BMR, while no relationship between tT 4 and BMR could be established (Stenlöf et al, 1993). Furthermore, research in birds revealed a positive link between T 3 and BMR (Chastel et al, 2003;Welcker et al, 2013) as well as standard metabolic rate (BMR +thermoregulatory costs; Duriez et al, 2004). When we used resting f H as a proxy for BMR, our results indicated a relationship between BMR and TH, as seasonal changes in resting f H were positively correlated with seasonal changes in T 3 and negatively correlated with those of T 4 .…”
Section: Discussionmentioning
confidence: 99%
“…(a) Study species and population The study was carried out between March and July 2005 on a free-living population of house sparrows that breed in nest boxes in Chizé, France (46809 0 N, 0824 0 W; Chastel et al 2003). A large proportion of the adults used in this study were first captured during the pre-breeding period using mist nets and marked with a unique metal ring and colour combination.…”
Section: Methodsmentioning
confidence: 99%